Microsoft SharePoint: Building Office 2007 Solutions in VB 2005 - Hillier, Scot (Apress, 2012)
With SharePoint now in its third release, many developers and users are well familiar with its core functionality. However, this version of SharePoint is truly astonishing in its scope. Not only does this version have the familiar sites, documents, and lists, but it also supports vast new capabilities in content management, document management, records management, and business intelligence. Along with these capabilities, this version of SharePoint has many new ways to integrate data and create customized solutions. For me, the combination of businessoriented capabilities and advanced solution-development techniques has always been the basis of my enthusiasm for SharePoint. In fact, this is the perspective that I have tried to bring to this book; I want to combine business needs and technical skills to create solutions that truly impact business. You can be the judge of how well that vision has been reached.